Advanced scanning probe lithography using anatase-to-rutile transition to create localized TiO2 nanorods - Kalb, Julian; Knittel, Vanessa; Schmidt-Mende, Lukas (Beilstein Journal of Nanotechnology, 2019)
In this article, we demonstrate the position-controlled hydrothermal growth of rutile TiO2 nanorods using a new scanning probe lithography method in which a silicon tip, commonly used for atomic force microscopy, was pulled across an anatase TiO2 film. This process scratches the film causing tiny anatase TiO2 nanoparticles to form on the surface. According to previous reports, these anatase particles convert into rutile nanocrystals and provide the growth of rutile TiO2 nanorods in well-defined areas. Due to the small tip radius, the resolution of this method is excellent and the method is quite inexpensive compared to electron-beam lithography and similar methods providing a position-controlled growth of semiconducting TiO2 nanostructures.
Keywords: hydrothermal crystal growth; lithography; nanostructures; seed crystals; surface processes; oxides